Worthy - Smith, Jada Pinkett, 1971- (Dey St., an imprint of William Morrow, 2023)
"A gripping, painfully honest, and ultimately inspirational memoir from global superstar and creator of the Red Table Talk series Jada Pinkett Smith. In a media driven landscape that crafts narratives for our celebrities, Smith recounts her story in an intimate conversation with readers. Along the way, she explores her path to accepting her power as a woman, and her discovery that a strong sense of self is every woman's right and saving grace. An impactful and rare memoir that engages and educates, Worthy is a courageous love song to self, to family, to life, and to the world. From an unconventional upbringing in Baltimore, to an unconventional marriage to one of the most famous men in the world, adhering to the status quo has never been a familiar road for Jada Pinkett Smith. In Worthy, Smith strips herself of all the labels and stories crafted by others, and reclaims her narrative with radical self-love. Worthy teaches us who Jada is, and how to embrace our most authentic lovable souls"--